Metrolinguistic Space, Youth and Identity: Implications for Linguistic and Language Education Research - Devkota, Kamal Raj; Sigdel, Jyoti (Education and Development, 2024)
This paper reports the findings of the research concerning how youth in a metropolitan context navigate a metrolinguistic space for constituting plurilingual identity. It applied content analysis as a methodological approach to investigating linguistic and multimodal information available in a metrolinguistic space. Besides, it applied a series of qualitative interviews with the key participants living in the metropolitan city, at least, for the last five years. Inspired by the theoretical and empirical scholarships of Appadurai (1996), Otsuji and Pennycook (2010) and Piccardo (2017), particularly relating the flows of different sorts (people, money, media, ideas, images, languages, ideologies) and identity, this research focused on how the migrant youth in Kathmandu metropolitan city navigated their linguistic identity across these flows. Three themes emerged from the analysis of the data: (a) contestant space of multiple languages, (b) creative construction of metrolingualism, and (c) creative linguistic and multimodal practices in various domains of life, all imperative in shaping youth identity(-ies) in the metropolitan context. The study further points out that metroethnicity and metrolinguistic features challenge monolingual and monocultural borders and shape the identity of the youth in the metropolitan context. Finally, in the light of these findings, this study draws some implications for linguistics and language education research.